Pulmonary Hypertension Subtypes and Mortality in CKD - Edmonston, Daniel L. (Am J Kidney Dis, 2019)
RATIONALE & OBJECTIVE. Pulmonary hypertension (PH) contributes to cardiovascular disease and mortality in patients with chronic kidney disease (CKD), but the pathophysiology is mostly unknown. This study sought to estimate the prevalence and consequences of PH subtypes in the setting of CKD. STUDY DESIGN. Observational retrospective cohort study. SETTING & PARTICIPANTS. We examined 12,618 patients with a right heart catheterization in the Duke Databank for Cardiovascular Disease from January 1, 2000 to December 31, 2014. EXPOSURES. Baseline kidney function stratified by CKD glomerular filtration rate (GFR) category and PH subtype. OUTCOMES. All-cause mortality. ANALYTICAL APPROACH. Multivariable Cox proportional hazards analysis. RESULTS. In this cohort, 73.4% of patients with CKD had PH, compared to 56.9% of patients without CKD. Isolated post-capillary PH (39.0%) and combined pre- and post-capillary PH (38.3%) were the most common PH subtypes in CKD. Conversely, pre-capillary PH was the most common subtype in the non-CKD cohort (35.9%). The relationships between mean pulmonary artery pressure, pulmonary capillary wedge pressure, and right atrial pressure with mortality were similar in both CKD and non-CKD cohorts. Compared to those with non-PH, pre-capillary PH conferred the highest mortality risk among patients without CKD (hazard ratio [HR], 2.27; 95% confidence interval [CI], 2.00 – 2.57). By contrast, in those with CKD, combined pre- and post-capillary PH was associated with the highest risk of mortality in CKD in adjusted analyses (compared to no PH, HRs of 1.89 [95% CI, 1.57 – 2.28], 1.87 [95% CI, 1.52 – 2.31], 2.13 [95% CI, 1.52 – 2.97], 1.63 [95% CI, 1.12 – 2.36] for GFR categories G3a, G3b, G4, and G5/G5D). LIMITATIONS. The cohort referred for right heart catheterization may not be generalizable to the general population. Serum creatinine data in the 6 months preceding catheterization may not reflect true baseline CKD. Observational design precludes assumptions of causality. CONCLUSIONS. In patients with CKD referred for right heart catheterization, PH is common and associated with poor survival. Combined pre- and post-capillary PH was common and portended the worst survival for patients with CKD.